Principles and objectives of information and analytical support for prenatal care - Мулеса, Оксана Юріївна; Снитюк, Віталій Євгенович; Герзанич, Святослав Омелянович (Eastern-European Journal of Enterprise Technologies, 2015)
IT-based prenatal care and outpatient counseling of pregnant women are aimed at more effective medical decisions and, therefore, a lower risk of medical errors and their consequences. A system analysis of contemporary clinical examination of pregnant women signals of lack of adequate valid information and analytical support for the medical sector. The technological models of hospitals and research institutions as well as the role of scientists in solving the problems of reproductive health require revision and normative regulation. The study has proved that the system of clinical examination and counseling of pregnant women has a complex structure; it is a multi-stage long process of interrelated decisions. We have decomposed the process into separate objectives and classified the latter. In general, all the relevant objectives may be classified as follows: objectives of classifying and clustering the objects, objective of structural and parametric identification of unknown dependencies, objectives of prognosis, and objectives of pre-processing the data and identifying informative features. We have provided the above stated objectives with correspondent mathematical models and analyzed the possibility of applying familiar methods. It is proved that objectives using subjective conclusions as input data should exploit an apparatus of the theory of fuzzy sets as well as relevant fuzzy models and methods of their solution.